Carbon Nanofibers with Embedded Sb2Se3 Nanoparticles as Highly Reversible Anodes for Na‐Ion Batteries. Issue 4 (29th December 2020) - Xia, Lishuang; Yang, Zhendong; Tang, Bin; Li, Feng; Wei, Jinping; Zhou, Zhen
Abstract: As a promising candidate for large‐scale energy storage, sodium‐ion batteries (SIBs) have superiority due to their low cost and abundance as a resource. Herein, homogeneous Sb2 Se3 nanocrystallites embedded in carbon nanofibers (Sb2 Se3 /CNFs) by electrospinning and selenization treatment are prepared. The obtained Sb2 Se3 /CNFs exhibit good cycling performance, high reversible capacity, and excellent rate capability as anodes for SIBs. The outstanding performances are attributed to a combination of Na + intercalation, conversion reaction, and alloying with Sb2 Se3, disclosed through in‐situ X‐ray diffraction. Meanwhile, unique nanostructures provide large contact surface and tolerant accommodation to volume expansion which bring high reversibility and long cycle durability. This distinctive material shows prospective applications of SIBs especially under high current density. Abstract : Sb2 Se3 embedded in carbon nanofibers (Sb2 Se3 /CNFs) are prepared by electrospinning and tested as anode materials for Na‐ion batteries. Owning to the superior structural flexibility and combined processes, Sb2 Se3 /CNFs deliver a stable capacity of 302 mAh g −1 at 1 A g −1 over 800 cycles and excellent rate performance (250 mAh g −1 at 10 A g −1 ), which are promising for large‐scale energy‐storage systems.